Google Earth Engine for Monitoring Drought Impacts on Urban Tree Using the Standardized Vegetation Index (SVI) in Amphoe Mueang, Nakhonratchasima Province, Thailand - Juntakut, Pongpun; Jantakat, Yaowaret; Jantakat, Chomphak (International Journal of Building, Urban, Interior and Landscape Technology, 2021)
The study aimed to apply the Google Earth Engine (GEE) for monitoring drought impacts on urban tree with the Standardized Vegetation Index (SVI) for long-term and near real-time period in Amphoe Mueang, Nakhonratchasima Province, Thailand. Terra/MODIS satellites from 2000 to recently were analyzed and accessed drought impacts on urban tree in the study area. The results of this study indicated that the SVI values (-2.50 to -1.50) in the condition of very high drought were found mostly in 2019, especially in summer season and with an increasing trend of higher drought in the middle of the study area (Tambon Nai Mueang) and in the south part of the study area (Tambon Nong Chabok, Pho Klang, and Nong Bua Sala) where should be seriously realized and considered on coming dry conditions. Based on the SVI timeseries, the condition of high drought (-1.5 to -0.5) was obviously found in years of 2002, 2005, 2015, 2016, and 2019. In addition, the study demonstrated that the GEE could display the SVI image of the whole timescale in the map section and can receive a pixel value from the visualized SVI images by clicking on a location within the study area in long-term and near real-time period. Conclusively, the application of the GEE for monitoring drought impacts on urban tree can be an efficiency tool for planning urban management to mitigate the impact of drought on urban tree and is helpful to take care of tree growth in urban area.